Connections between health research systems and decision-making spaces: lessons from the COVID-19 pandemic in the province of Québec, Canada - Pernelle Smits; Caroline Cambourieu; Mathieu Ouimet (BMC, 2023)
Abstract The coronavirus 2019 (COVID-19) pandemic allowed for exceptional decision-making power to be placed in the hands of public health departments. Data and information were widely disseminated in the media and on websites. While the improvement of pandemic management is still a learning curve, the ecosystem perspective - that is, the interconnection of academic health research systems and decision-making spaces - has received little attention. In this commentary, we look at the mechanisms in place, or not, in Canada for ensuring decision-making spheres can "speak" to academic research systems. We look at the thick walls that are still in place between health research systems and decision-making spaces. More precisely, we discuss three organizational flaws that we identified in the evidence-informed decision-making ecosystem of Québec and, more broadly, Canada. We introduce some inspiring measures that other countries have implemented to better link evidence and public health decision-making during health crises. The observed flaws and options are related to the vitality of early information sharing relays, the cross-sectional capacity to issue opinions, and the collection and integration of hard and soft data.